Transcriptomic analysis of Medicago truncatula calli with MtWOX9-1 overexpression - V. E. Tvorogova; E. Y. Krasnoperova; A. A. Kudriashov; K. A. Kuznetsova; E. A. Potsenkovskaya; Y. A. Fedorova; L. A. Lutova (Вавиловский журнал генетики и селекции)
Somatic embryogenesis (SE) is the development of embryo-like structures from somatic plant tissues. This process rarely can be observed in nature, but for many plant species, in vitro protocols are developed, which allow to obtain somatic embryos formation directly from tissues of plant explant or from the embryogenic callus. SE is widely used for plant propagation and transformation; therefore, the search for SE stimulators and revealing of the mechanisms of their functioning are very important for biotechnology. Among the SE regulators, proteins of the WOX family play significant roles. WOX (WUSCHEL-RELATED HOMEOBOX) is a homeodomain-containing transcription factor family. Different WOX genes  function  in different plant organs  and tissues, maintaining meristem activity and regulating cell proliferation  and differentiation. Recently, we have shown  that  transcription factor MtWOX9-1, belonging to the WOX family, can stimulate SE in the Medicago truncatula callus culture. In this research, transcriptomic analysis of highly embryogenic calli with MtWOX9-1 overexpression was performed in comparison to wildtype calli. It was shown that MtWOX9-1 overexpression led to the activation  of several groups  of genes,  including genes  related  to cell division, tissue differentiation, and seed development. Enriched GO pathways included  several groups  related to histone  methyltransferase activity as well as DNA methylation and chromatin binding,  suggesting major epigenetic changes that  occur in call overexpressing MtWOX9-1. Using Medicago Truncatula Gene Expression Atlas, we also identified a group of genes  coding for transcription factors that were both coexpressed with MtWOX9-1 in different plant organs  and differentially expressed in our samples. These genes  are putative targets of MtWOX9-1, and they may act in the same pathway with this regulator during SE.